PARAGENESIS AND COMPOSITION OF BANALSITE, STRONALSITE, AND THEIR SOLID SOLUTION IN NEPHELINE SYENITE AND ULTRAMAFIC ALKALINE ROCKS - Liferovich R.P.; Mitchell R.H.; Zozulya D.R.; Shpachenko A.K. (My University, 2006)
The paragenesis and compositional variation of banalsite-stronalsite solid-solution series, Ba1-xSrx Na2Al4Si4O16, from five new occurrences in nepheline syenite and ultramafic alkaline rocks are characterized; we also present new data for banalsite and stronalsite from the Benallt mine, in Wales, UK, Långban, in Sweden, a Khibina, in the Kola Peninsula, Russia. Commonly, members of the banalsite-stronalsite solid-solution series occur at the periphery of nepheline crystals in contact with late analcime or albite, and form zoned aggregates grading from banalsite in the cores to barian stronalsite and stronalsite at the margins. Textural relationships show that banalsite might form at a late-magmatic stage, together with nepheline, whereas stronalsite preferentially forms as a by product of the postmagmatic conversion of nepheline to analcime, replacing both nepheline and banalsite. This process is facilitated by the similarity of the crystal structures of nepheline and these Bal-x, SrxNa2Al4 Si4O16 tectosilicates, both of which are based on infinite Si-Al ordered frameworks consisting of -UDUD-rings. The complete Bal-x SrxNa2Al4Si4O16 solid solution and very limited solid solution with lisetite, CaNa2Al4Si4016, result from the topological similarity of the structures of banalsite and stronalsite, and significant differences with that of lisetite with respect to cation order.
Keywords: ALTERATION; BANALSITE; GREMYAKHA-VYRMES; IJOLITE; LåNGBAN; NEPHELINE; PILANSBERG; PRAIRIE LAKE; SAKHARJOK; STRONALSITE; SYENITE; TURIY MYS